Effects of Ce0.6Mn0.3Fe0.1O2-δ Interlayer on Electrochemical Properties of Microtubular SOFC Using Doped LaGaO3 Electrolyte. Issue 12 (15th September 2015) - Hosoi, Kohei; Sakai, Takaaki; Ida, Shintaro; Ishihara, Tatsumi
Abstract : Effects of Ce0.6 Mn0.3 Fe0.1 O2-δ (CMF) anodic interlayer on power generation properties of microtubular SOFC using doped La0.9 Sr0.1 Ga0.8 Mg0.2 O3 (LSGM) electrolyte were investigated. Two types of microtubular cells, which were used NiO-Ce0.8 Gd0.2 O2- δ (GDC) cerment for anode porous substrate, were prepared with (A-cell) or without (B-cell) CMF interlayer by dip-coating method. The power generation properties of A- and B-cell sintered at 1623 K were measured. It was revealed that A-cell showed about 40% higher power density (1 W/cm 2 at 973 K) than that of B-cell at temperature from 873 to 973 K because of the decreased electrode polarization by introducing CMF anodic interlayer. It was found that the diffusion of Ni into LSGM/Ti-LDC (Ce0.6 La0.4 O2- δ added with 0.5 wt% TiO2 ) interlayer was much suppressed by CMF interlayer (A-cell). This is because Ni was trapped in the CMF interlayer and formed Ni-CMF composite layer. Decrease in the polarization resistance might be assigned to the formation of Ni-CMF composite layer. Thus, CMF is promising for increasing the power generation property of microtubular SOFC using LSGM electrolyte prepared by dip coating method.